(untitled) (Revista de Ensino em Artes, Moda e Design, 2020)
The present study displays the result of the application of the methodological phases of the MODThink model by Emídio (2018), in the context of an academic project of the first year of the Fashion Design course at the State University of Londrina. Through the application of the bionic creativity tool, it demonstrates how it was possible to include the concept of the project in product modeling, in addition to contributing to aspects of addressed to sustainability.